Student Pharmacists during the Pandemic: Development of a COVID-19 Knowledge, Attitudes, and Practices (COVKAP) Survey - Alina Cernasev; Meghana Desai; Lauren J. Jonkman; Sharon E. Connor; Nicholas Ware; M. Chandra Sekar; Jon C. Schommer (MDPI AG, 2021)
Background: The COVID-19 pandemic has caused innumerable changes to all aspects of human life and behavior, including academic life. This study describes the development of a COVID-19 Knowledge, Attitudes, and Practices (COVKAP) Survey among U.S. student pharmacists. The survey was administered at Doctor of Pharmacy programs in three states-Tennessee, Ohio, and Pennsylvania. Methods: The COVKAP survey-an online cross-sectional survey-was distributed to U.S. student pharmacists enrolled in three different colleges of pharmacy in three states during the fall semester of 2020. The survey was developed using literature review and Dillman's recommendations for survey design. The COVKAP survey consisted of 23 closed and Likert-scale questions, and three open-ended questions. The research team conducted descriptive and inductive thematic analyses on the quantitative and qualitative data, respectively using SPSS (v27) and Dedoose® software. Results: A total of 421 responses were received. Respondents were predominantly female (72%) and White (79%). The average age of respondents was 23.4 years. The qualitative analysis revealed three themes: (1) Wellbeing and mental health struggles; (2) Being part of the decision-making process; (3) Necessity of adequate protection measures. Conclusions: Preliminary study findings indicate that student pharmacists' concerns and the challenges that they face in their academic pursuits are largely similar across the three states in this study and inform about the importance of recognizing and mitigating the impact of widespread disruption in education. This disruption provides an opportunity for pharmacy academia to examine practices and methods that can be improved upon to help students become successful practitioners.